Long-term outcome after combined kyphoplasty and intraoperative radiotherapy (Kypho-IORT) for vertebral tumors - Bludau, Frederic; Winter, Laura; Welzel, Grit; Obertacke, Udo; Schneider, Frank; Wenz, Frederik; Ruder, Arne Mathias; Giordano, Frank Anton (Radiation oncology, 2020)
The spine represents the site which is most frequently affected by bone metastases in patients with systemic cancer. Of all local treatment options, combined kyphoplasty and intraoperative radiotherapy (Kypho-IORT) provides both, instantaneous stabilization and immediate pain relief. We here report on the long-term outcomes of the largest cohort treated with Kypho-IORT to date.